Effect of injecting adipose stem cells combined with platelet-rich fibrin releasate at Shenshu acupoint (BL23) on acute kidney injury in rabbits - Chuang, Hsin-Ni; Pei, Wen; Kuo, Tzong-Fu; Liu, Yu-Hao; Wang, Chia-Yih; Chang, Yen-Wei; Chuang, Chi‐Hsuan; Yang, Chang-Huan; Chuang, Ming-Hsi (Frontiers in Pharmacology, 2025)
IntroductionAcute kidney injury (AKI) is a major and unmet medical need, characterized by a sudden onset of kidney dysfunction that often occurs within 7 days. Adipose-derived stem cells (ADSCs) are known for their regenerative, differentiative, and repair abilities, making them a promising therapeutic option for kidney injury. Platelet-rich fibrin releasate (PRFr), derived from platelet-rich fibrin after static incubation, contains numerous growth factors that may promote the differentiation and proliferation of stem cells. Additionally, acupoints such as Shenshu (BL23) have been used in clinical practice and experimental settings, particularly in renal failure treatments.MethodsThis study aimed to evaluate the synergistic effects of ADSCs and PRFr, administered separately or in combination, at the Shenshu acupoint (BL23) in New Zealand white rabbits with acute kidney injury. The treatment groups were injected with ADSCs, PRFr, or a combination of both. Serum creatinine (CRE) and blood urea nitrogen (BUN) levels were measured to assess kidney function. Additionally, histological examination of kidney tissue was performed to observe morphological changes and tissue repair.ResultsThe PRFr + ADSCs treatment group exhibited a significant reduction in CRE and BUN levels during the second week following transplantation. After 7 weeks of treatment, the PRFr + ADSCs group showed the most favorable kidney repair outcomes, with intact glomeruli, no edema or vacuole-like changes in the renal tubular epithelial cells, and no significant infiltration of inflammatory cells in the surrounding tissues.DiscussionThe administration of PRFr, ADSCs, and their combination at the Shenshu acupoint (BL23) demonstrated a potential therapeutic effect in repairing damaged renal cells, improving kidney function, and reducing serum CRE and BUN levels. These findings suggest that injection of PRFr, ADSCs, and their combination at the Shenshu acupoint (BL23) can effectively repair damaged renal cells and improve kidney function in AKI. The observed synergistic effect indicates that this approach holds potential as a novel therapeutic strategy for kidney injury. Further research is needed to optimize treatment protocols and elucidate the underlying mechanisms.